Investigation of corrosive influence on the fatigue behaviour of HFMI-treated and as-welded transverse non-load-carrying attachments made of mild steel S355. (October 2021) - Weinert, Joscha; Gkatzogiannis, Stefanos; Engelhardt, Imke; Knoedel, Peter; Ummenhofer, Thomas
Highlights: Study of the corrosion influence on the effectiveness of HFMI. Application of laboratory tests to simulate real marine corrosion conditions. Change of surface condition, weld geometry and stress concentration due to corrosion. Significantly increase of fatigue life in corrosive environment by using HFMI. Present first-step investigation clarifies the next steps to be taken. Abstract: This study reports on the corrosion fatigue behaviour of fillet welds in the as-welded and the high frequency mechanical impact (HFMI) treated condition. For this purpose, transverse attachment specimens made of steel S355J2+N were investigated. Seawater corrosion was simulated by immersing the specimens in artificial seawater and by the salt spray chamber test. Sequential and simultaneous corrosion fatigue tests were carried out on the corroded specimens under axial and bending loading. FEM simulations show that the stress concentration factors are reduced due to the corrosion-related change in HFMI-treated weld geometry. HFMI significantly improves fatigue life in all investigated cases.